2021
DOI: 10.11591/ijeecs.v22.i2.pp1078-1086
|View full text |Cite
|
Sign up to set email alerts
|

Transfer learning with GoogLeNet for detection of lung cancer

Abstract: <p class="p1">The use of computer algorithms has gained momentum in filling/assisting roles of specialists especially in early diagnosis scenarios. This paper proposes the employment of deep neural networks (DNN) to detect images with malignant nodules of lung computed tomography (CT). The method includes subjecting input images to a simple and fast pre-processing which isolates regions of interest (ROI), that’s the lungs dominated area, ridding the images of other surrounding tissues and artefacts. Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…According to a literature survey [32] a transfer learning method can currently be adopted to improve the performance of traditional machine learning methods by transferring information from a related domain. There are many applications that successfully applied transfer learning to enhance the model performance, e.g., sports video classification using pre-trained neural network [33], classification of lung cancer using pre-trained convolutional neural networks [34], automated fruit recognition using pre-trained models [35], and plant leaf disease classification using a pre-trained model [36]. As suggested in [37], for improving the CNN model with the tranfer learning technique, a pre-trained model, namely EfficientNet-B0, which is suitable with the dataset used in this study (image size of 224x224 pixel), was used.…”
Section: Improving Cnn Model Performance Using Transfer Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a literature survey [32] a transfer learning method can currently be adopted to improve the performance of traditional machine learning methods by transferring information from a related domain. There are many applications that successfully applied transfer learning to enhance the model performance, e.g., sports video classification using pre-trained neural network [33], classification of lung cancer using pre-trained convolutional neural networks [34], automated fruit recognition using pre-trained models [35], and plant leaf disease classification using a pre-trained model [36]. As suggested in [37], for improving the CNN model with the tranfer learning technique, a pre-trained model, namely EfficientNet-B0, which is suitable with the dataset used in this study (image size of 224x224 pixel), was used.…”
Section: Improving Cnn Model Performance Using Transfer Learningmentioning
confidence: 99%
“…In transfer learning, the knowledge of existing trained models is transferred to build new classification models. There are several research studies that investigated on classification performance when using transfer learning, e.g., sports video classification using pre-trained neural network [33], classification of lung cancer based on CNN and transfer learning with GoogLeNet [34], fruit recognition using pre-trained models [35], and leaf disease classification based on a pre-trained model [36]. In research Ramesh and Mahesh [33], reported the comparison performance results between a CNN model and a pre-trained CNN model for classifying sports categories from video collected from YouTube.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have demonstrated a promising alternative method known as transfer learning to overcome these obstacles. Transfer learning means improving the learning of a new task through transferring knowledge from a previously learned task [25]. The fundamental goal of this research is to compare the performance of pre-trained ResNet50 against the modified residual network in detecting and automatically classifying Alzheimer's disease using MRI scans.…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%
“…This is an important area of research because during conventional examination by a radiologist, non-cancerous lesions can be misclassified as a cancer (false-positive), while malignancies may be missed (false-negative) resulting in radiologists failing to detect between 10% and 30% of breast cancers cases. Computer aided diagnosis (CAD) is aimed to speed up and enhance the diagnosis process via assisting specialists in the detection and classification of the breast cancer by deploying scalable computerized diagnostic tools, hence, restricting the occurrence of human related shortcomings (AL-Huseiny & Sajit, 2021;Batra et al, 2020;Jalalian et al, 2013;Tan, Sim & Ting, 2017). The introduction of computerized approaches into medical procedures is highly reliant on the sensing mechanisms.…”
Section: Introductionmentioning
confidence: 99%